Elective extra corporeal membrane oxygenation for high-risk rigid bronchoscopy. Issue 11 (24th July 2020) - Martinod, Emmanuel; Portela, Ana-Maria; Uzunhan, Yurdagül; Freynet, Olivia; Abou Taam, Salam; Vinas, Florent; Dominique, Stephane; Tandjaoui-Lambiotte, Yacine; Otero-Lopez, Manuel; Zogheib, Elie; Lebreton, Guillaume
Abstract : The use of extracorporeal membrane oxygenation for high-risk rigid bronchoscopy has been reported in few urgent cases. We report our experience with this approach which was planned electively in five cases on 202 procedures (2.5%). It was proposed because of the potential inability to ventilate the lungs using conventional techniques due to extensive tracheobronchial lesions or the risk of major intraoperative bleeding related to disease characteristics. There were no intraoperative complications and postoperative course was favourable in all patients. With a maximum follow-up of 3 years and 7 months, all patients are alive with no tracheostomy despite major morbidities.